Automotive Battery Technology - Thaler, Alexander; Watzenig, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The use of electrochemical energy storage systems in automotive applications also involves new requirements for modeling these systems, especially in terms of model depth and model quality. Currently, mainly simple application-oriented models are used to describe the physical behavior of batteries. This book provides a step beyond of state-of-the-art modeling showing various different approaches covering following aspects: system safety, misuse behavior (crash, thermal runaway), battery state estimation and electrochemical modeling with the needed analysis (pre/post mortem). All this different approaches are developed to support the overall integration process from a multidisciplinary point-of-view and depict their further enhancements to this process.
Electrochemical battery modeling -- Battery management systems -- Aging of batteries -- Design of experiments and statistical analysis for batteries -- Impedance modeling -- Crashworthiness of batteries -- Thermal abuse of batteries.
Keywords: Engineering; Chemistry; Engineering; Automotive Engineering; Energy Storage; Electrochemistry